Dicitrinone D, an antimitotic polyketide isolated from the marine-derived fungus Penicillium citrinum. Issue 40 (5th October 2017) - Chen, Li; Zhao, Yang-Yang; Lan, Rong-Feng; Du, Lin; Wang, Bing-Shuai; Zhou, Tong; Li, Ya-Ping; Zhang, Qi-Qing; Ying, Min-Gang; Zheng, Qiu-Hong; Liu, Qin-Ying
Abstract: Dicitrinone D is a novel polyketide isolated from a marine-derived fungus Penicillium citrinum . In this study, we described the isolation, structure elucidation and antitumor mechanism of this compound. Cell proliferation assay showed that dicitrinone D was safe for normal cells, but effectively inhibited the growth of multiple tumor cells, especially SPC-A1 cells. Cell cycle and immunofluorescence analysis suggested that dicitrinone D had cellular effects similar to other microtubule-targeting agents. Polymerization assay, electron microscopy and time-lapsed video microscopy assay demonstrated dicitrinone D was a microtubule-destabilizing agent. Finally, the docking analysis predicted that dicitrinone D may bind to vinblastine binding site on tubulin. Graphical abstract: